2021
DOI: 10.1021/acs.jpcb.0c11162
|View full text |Cite
|
Sign up to set email alerts
|

Transient Diffusive Interactions with a Protein Crowder Affect Aggregation Processes of Superoxide Dismutase 1 β-Barrel

Abstract: Aggregate formation of superoxide dismutase 1 (SOD1) inside motor neurons is known as a major factor in onset of amyotrophic lateral sclerosis. The thermodynamic stability of the SOD1 β-barrel has been shown to decrease in crowded environments such as inside a cell, but it remains unclear how the thermodynamics of crowding-induced protein destabilization relate to SOD1 aggregation. Here we have examined the effects of a protein crowder, lysozyme, on fibril aggregate formation of the SOD1 β-barrel. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…More recently, Iwakawa et al studied the effect of a negatively charged crowding agent, lysozyme, on SOD1 b-barrel structure and oligomerization. Lysozyme slowed down the protein oligomerization, while NMR analysis of the monomer revealed that the interactions between lysozyme and SOD1 stabilized the latter in alternative excited state [1368].…”
Section: Protein Folding Quinary Structure and Large Assembliesmentioning
confidence: 99%
“…More recently, Iwakawa et al studied the effect of a negatively charged crowding agent, lysozyme, on SOD1 b-barrel structure and oligomerization. Lysozyme slowed down the protein oligomerization, while NMR analysis of the monomer revealed that the interactions between lysozyme and SOD1 stabilized the latter in alternative excited state [1368].…”
Section: Protein Folding Quinary Structure and Large Assembliesmentioning
confidence: 99%
“…The cleft between 5 and 6 was reported to become partially unstructured in excited states of certain destabilized mutants of the full-length apoSOD1 monomer, which might potentially lead to nonnative oligomerization [ 7 ]. In addition, some of these conformations might be related to a compact excited state of SOD1 which was detected by NMR experiments [ 13 ] and found to be stabilized by transient interactions with a protein crowder, leading to a slow-down of SOD1 aggregation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The loop truncation entropically stabilizes SOD1 relative to the full-length disulfide-reduced apoSOD1 monomer [ 12 ]. To bring the stability of SOD1 closer to that of the disulfide-reduced apoSOD1 monomer, the isoleucine 35 to alanine (I35A) mutation is often introduced to the barrel [ 9 , 16 , 17 ], substantially decreasing the thermal stability of SOD1 and causing a large part of SOD1 molecules to be unfolded in the cell at 37 degrees Celsius [ 9 ]. Thus, although the I35A mutation is currently not known to cause familial ALS, the SOD1 mutant constitutes a convenient model system to investigate the effects of the cellular environment on the folding state of the destabilized apoSOD1 monomer.…”
Section: Introductionmentioning
confidence: 99%
“…26 Another NMR study found reduced aggregation of SOD1 in the presence of protein crowders. 27 This was interpreted to result from SOD1− crowder interactions that were competing with SOD1 aggregation as one example of crowding-induced effects on aggregation covered more generally in a theoretical analysis. 28 Homing in on biological function, a FRET-based analysis contrasts binding of Hsp70 and Hsc70 to a model protein substrate in living cells in the cellular background of other functional interactions of Hsc70.…”
Section: Central In Many Biological Functions Are Protein Interactionsmentioning
confidence: 99%
“…Direct evidence of how the binding energetics of a peptide to an SH3 domain is modulated by the presence of different protein crowders or osmolytes comes from an NMR study . Another NMR study found reduced aggregation of SOD1 in the presence of protein crowders . This was interpreted to result from SOD1–crowder interactions that were competing with SOD1 aggregation as one example of crowding-induced effects on aggregation covered more generally in a theoretical analysis .…”
mentioning
confidence: 99%